Polyvinylidene fluoride-based composite membrane as well as preparation method and application thereof

By using polyvinylidene fluoride (PVDF) and fluorinated nanosilicon dioxide (F-SiO2) nanoparticles blending technology in seawater desalination, an ultra-thin PVDF/F-SiO2 composite film was prepared, which solved the problems of insufficient hydrophobicity and poor wetting resistance of existing film materials, and achieved efficient seawater desalination performance and stability.

CN119701684AActive Publication Date: 2025-03-28WUHAN UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411902761.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing membrane materials have insufficient hydrophobicity and poor resistance to wetting in the internal structure of the membrane in seawater desalination, resulting in low salt cutoff and poor stability of seawater desalination. At the same time, the large film thickness leads to low water flux.

Method used

An ultra-thin PVDF/F-SiO2 composite film was prepared by blending polyvinylidene fluoride (PVDF) and fluorinated nanosilicon dioxide (F-SiO2) nanoparticles by adjusting the PVDF concentration, the addition amount of F-SiO2 nanoparticles and the composition of the solidification bath. This film forms high porosity and excellent anti-imbrication properties by spreading the film into the solidification bath.

Benefits of technology

The hydrophobicity and anti-infiltration properties of the membrane are significantly improved, the salt cutoff rate and water flux are improved, and the film thickness is reduced, achieving long-term stability and efficient performance during seawater desalination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701684A_ABST
    Figure CN119701684A_ABST
Patent Text Reader

Abstract

The invention provides a polyvinylidene fluoride-based composite membrane as well as a preparation method and application thereof. The preparation method of the polyvinylidene fluoride-based composite membrane comprises the following steps: extruding and spreading a polyvinylidene fluoride-based composite dispersion liquid on the surface of a coagulating bath solution, curing to form a membrane, and drying to obtain the polyvinylidene fluoride-based composite membrane. The polyvinylidene fluoride-based composite dispersion liquid is formed by dissolving polyvinylidene fluoride and fluorinated nano silicon dioxide and dispersing the solution into a solvent, and the mass percent concentration of the polyvinylidene fluoride is 10-13.5 wt%; the coagulating bath solution is formed by dissolving a solvent in water, and the mass ratio of the solvent to the water is (50-70): (50-30) in percentage by mass. By improving the hydrophobicity of the surface of a polymer skeleton in the membrane, the infiltration resistance of holes in the membrane is improved, the salt rejection rate is remarkably increased, and pollution of salt scales to the holes in the membrane is retarded, so that long-time stable work in the seawater desalination process is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of membrane distillation seawater desalination, and in particular to a polyvinylidene fluoride composite membrane and a preparation method and application thereof. Background Art

[0002] With the rapid growth of the global population and the continuous development of industry, the shortage of fresh water resources has become an imminent key issue, and seawater desalination has become one of the most effective solutions. Among them, the garrison of my country's remote islands and reefs is crucial in building a "maritime power", but conventional commercial reverse osmosis technology, multi-effect distillation and multi-stage flash evaporation all require a large equipment space and a continuous supply of electricity and heat energy, which has certain limitations. Therefore, membrane distillation (MD) technology, which can efficiently utilize low-quality thermal energy (including renewable energy: solar energy, geothermal energy, etc.), has a good application prospect for seawater desalination. Membrane distillation desalination is based on the vapor pressure difference on both sides of the membrane. Low temperature drives water vapor through the hydrophobic porous membrane, so that the non-volatile salt remains in the feed solution, achieving efficient desalination, and is insensitive to salt concentration, and the equipment is simple. Therefore, the hydrophobic porous membrane is the key to membrane distillation technology, which can maintain the liquid-gas interface on the membrane surface, making the process of vaporizing seawater stable and efficient. However, the main problems of traditional polymer hydrophobic porous membranes in seawater desalination are low flux and membrane pore wetting, which lead to membrane fouling and scaling, affecting the stability of seawater desalination, making it difficult for membrane distillation technology to break through the synergistic improvement of flux and stability. Therefore, improving the hydrophobicity of hydrophobic porous membranes is an effective way to ensure that the porous membranes are not wetted and achieve improved stability of seawater desalination.

[0003] To improve the hydrophobicity of hydrophobic porous membranes, super-hydrophobic surface modification is usually used, and the micro-nano structure of the lotus leaf surface is used to form an air layer between the rough surface and the water, thereby achieving the effect of stabilizing the liquid-gas interface. However, the super-hydrophobic surface will still face the consumption of the air layer under the long-term membrane distillation process, resulting in the membrane pores being infiltrated, unable to effectively inhibit the passage of brine, and losing the stability of seawater desalination. Therefore, the strategy of using composite nanofillers can simultaneously improve the surface and regulate the pore structure to alleviate the infiltration of the membrane pores and improve the stability of membrane distillation. Based on the blending of nanofillers and polymers, the roughness of the membrane surface can be improved to form a micro-nano structure, while bringing a certain rough structure to the inner wall surface of the pores, forming an air layer between the membrane surface and the water to support the liquid-gas interface on the surface of the hydrophobic membrane. Commonly used nanofillers include carbon nanotubes and hydrophobically modified fillers (silicon dioxide, titanium dioxide, calcium carbonate and MXene). For example, the electrospinning composite membrane adopts the micro-nano structure of the fiber surface to achieve high porosity and anti-infiltration performance under large pores, effectively slowing down the reduction of flux. Professor Lan of the University of Ottawa in Canada used a polyvinylidene fluoride composite porous membrane with hydrophobic silica nanoparticles. In the film-forming process of non-solvent induced phase separation, the hydrophobic silica particles were embedded in the membrane surface and matrix, and the surface micro-nano structure was regulated to form an air layer on the membrane surface, which effectively resisted the infiltration of water into the membrane pores (Effects of superhydrophobicSiO2nanoparticles on the performance of PVDF flat sheet membranes for vacuum membrane distillation, Desalination 2015, 373, 47, https: / / doi.org / 10.1016 / j.desal.2015.07.002). In addition, due to the presence of the air layer, the liquid-gas interface area is increased, and the vaporization area is increased, thereby achieving the effect of improving the flux of membrane distillation. Therefore, the hydrophobic silica particles composite polyvinylidene fluoride porous membrane with a thickness of 100 μm was used for membrane distillation desalination of 35 g / L sodium chloride solution at 27 °C, and the desalination efficiency was 2.9 kg / m 2 The flux of ·h is 4 times higher than that of pure PVDF porous membrane, and the salt rejection rate is as high as 99.98%.

[0004] Based on this strategy, Professor Kwon of the Ulsan Institute of Science and Technology in South Korea proposed the construction of a polyvinylidene fluoride composite membrane composited with MXene nanosheets (Holistic approach for fabrication ofsuperhydrophobic MXene-based membrane for enhanced membrane distillation, Desalination 2024, 580, 117536, https: / / doi.org / 10.1016 / j.desal.2024.117536). Based on non-solvent induced phase separation, MXene nanosheets are concentrated on the surface of the porous membrane and in the matrix, and a composite membrane with a thickness of 289μm is obtained. MXene nanosheets mainly construct a hierarchical micro-nano structure on the surface of the polyvinylidene fluoride membrane. Its rough surface promotes the formation of an air layer on the surface, achieves an improvement in hydrophobicity, obtains a water contact angle of more than 143°, and has the advantage of self-cleaning. Therefore, the presence of the surface air layer effectively inhibits the infiltration of water into the membrane pores and increases the effective volatile interface area. In the membrane distillation desalination of 35g / L sodium chloride solution at 70°C, the water flux reaches 8kg / m 2 ·h.

[0005] However, although the hydrophobic composite porous membrane can use the surface micro-nano structure formed by nanofillers to inhibit membrane pore infiltration, they still face the problem of low flux due to the extra water vapor transmission resistance provided by the air layer on the membrane surface. In addition, the hydrophobic properties brought by the surface micro-nano structure are still facing the exhaustion of the air layer, so the membrane distillation hydrophobic porous membrane requires a certain thickness to ensure that the air layer is not broken by long-term membrane distillation. The thickness of the membrane is also related to the water vapor transmission distance and has the potential to increase the flux. Therefore, the traditionally prepared hydrophobic porous membranes are mostly between 50 and 400μm, which makes it difficult to reduce the membrane thickness while ensuring hydrophobicity, so as to break through the limitations of the hydrophobic porous membrane's membrane pore anti-infiltration and increase the membrane distillation flux. Summary of the invention

[0006] In view of this, the present invention proposes a polyvinylidene fluoride-based composite membrane and a preparation method and application thereof, in order to solve the problems of insufficient hydrophobicity of existing membrane materials, poor anti-wetting property of the internal structure of the membrane, resulting in low salt interception rate and poor stability of membrane distillation seawater desalination, while reducing the membrane thickness to improve its water flux.

[0007] In a first aspect, the present invention provides a method for preparing a polyvinylidene fluoride based composite film, comprising: extruding and spreading a polyvinylidene fluoride based composite dispersion on the surface of a coagulation bath solution, curing to form a film, and drying to obtain a polyvinylidene fluoride based composite film;

[0008] The polyvinylidene fluoride composite dispersion is formed by dissolving and dispersing polyvinylidene fluoride and fluorinated nano-silicon dioxide in a solvent, and the mass percentage concentration of the polyvinylidene fluoride is 10 to 13.5 wt %;

[0009] The coagulation bath solution is formed by dissolving a solvent in water, and the mass ratio of the solvent to the water is 50-70:50-30 in terms of mass percent.

[0010] On the basis of the above technical solution, preferably, the fluorinated nano-silica accounts for 5 to 13 wt% of the mass of the polyvinylidene fluoride; the fluorinated nano-silica is selected from hydrophobic fluorinated nano-silica with a particle size of 7 to 40 nm.

[0011] On the basis of the above technical solution, preferably, the solvent is selected from at least one of N-methylpyrrolidone, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, cyclohexanone and tetrahydrofuran.

[0012] In the second aspect, the present invention relates to a polyvinylidene fluoride based composite membrane prepared by the above method, wherein the polyvinylidene fluoride based composite membrane has a thickness of 6.6 to 22.1 μm, a porosity of 59.7 to 69.8%, a pore size of 175 to 204 nm, a water contact angle of 116 to 132°, and a water liquid osmotic pressure of 1.39 to 1.94 bar.

[0013] In a third aspect, the present invention also relates to the application of polyvinylidene fluoride based composite membrane in seawater desalination.

[0014] In a fourth aspect, the present invention provides a seawater desalination system, including a membrane distillation seawater desalination device, and also including the above-mentioned polyvinylidene fluoride-based composite membrane.

[0015] On the basis of the above technical solution, preferably, the membrane distillation seawater desalination device comprises a membrane module, and the membrane module is used to equip a polyvinylidene fluoride-based composite membrane.

[0016] In a fifth aspect, the present invention provides a method for desalination of seawater based on the above system, the method comprising: circulating the heated seawater in the system, condensing it, and obtaining desalinated seawater.

[0017] In a sixth aspect, the present invention also relates to a method for evaluating the stability of a seawater desalination system, the method comprising:

[0018] Evaluating the stability of the seawater desalination system according to the salt rejection rate and water flux of the polyvinylidene fluoride based composite membrane;

[0019] The salt rejection rate of the polyvinylidene fluoride-based composite membrane is calculated by the salt content of the initial seawater and the salt content of the water collected after condensation, and the calculation formula is shown in formula (I):

[0020] R=(1-C P / C F )×100% (I),

[0021] In formula (I), R is the salt rejection rate, C F is the initial seawater salinity, C P is the salt content of the water collected after condensation;

[0022] The water flux of the polyvinylidene fluoride-based composite membrane is the mass of water collected after condensation.

[0023] On the basis of the above technical solution, preferably, in the process of desalinating seawater, the salt rejection rate of the polyvinylidene fluoride based composite membrane is 89.6-99.9%, and the water flux is 10.06-22.58 kg / m 2 ·h.

[0024] The polyvinylidene fluoride based composite film provided by the present invention and its preparation method and application have the following beneficial effects compared with the prior art:

[0025] (1) In order to improve the performance of membrane distillation desalination, the prior art usually requires complex and unstable hydrophobic modification of the membrane surface. The present invention focuses on improving the hydrophobicity of the surface of the polymer skeleton in the membrane, greatly improving the anti-infiltration property of the pores in the membrane, significantly improving the salt rejection rate, and blocking the pollution of salt scale to the pores in the membrane, thereby achieving long-term stable operation in the seawater desalination process.

[0026] (2) The present invention can achieve the improvement of the stable anti-wetting performance of the PVDF / F-SiO2 composite membrane without complicated post-processing. By adjusting the concentration of polyvinylidene fluoride (PVDF), the amount of hydrophobic fluorinated nano-silica (F-SiO2) nanoparticles added and the composition of the coagulation bath, the thickness, pore size and anti-wetting performance of the PVDF / F-SiO2 composite membrane can be controlled.

[0027] (3) The existing technical modification requires a thicker membrane to solve the structural instability problem caused by the modification. Too high a thickness will lead to a decrease in water flux. The present invention prepares an ultra-thin PVDF / F-SiO2 composite membrane, which solves the problem of flux decrease usually caused by traditional modification and achieves a synergistic improvement in water flux and stability performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 A schematic diagram of a membrane distillation seawater desalination device provided by the present invention;

[0030] Figure 2 This is a cross-sectional scanning electron microscope (SEM) in-hole scanning magnified image of Example 2 provided by the present invention;

[0031] Figure 3 This is a cross-sectional scanning electron microscope (SEM) in-hole scanning magnified image of Comparative Example 1 provided by the present invention;

[0032] Figure 4 This is a cross-sectional scanning electron microscope (SEM) in-hole scanning magnified image of Comparative Example 2 provided by the present invention;

[0033] Figure 5 A schematic diagram of the principle of membrane distillation seawater desalination using the polyvinylidene fluoride based composite membrane prepared by the present invention;

[0034] Figure 6 This is a stability test chart of different membrane materials provided by the present invention under the same conditions. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The present invention adopts the preparation method of the polymer membrane of the disclosed invention patent (authorization announcement number: CN1 16751382B), realizes the uniform and stable attachment of F-SiO2 nanoparticles on the surface of the PVDF skeleton, and greatly improves the hydrophobicity of the internal skeleton of the PVDF / F-SiO2 composite membrane. The basic principles for the uniform and stable attachment of F-SiO2 nanoparticles to the surface of the PVDF skeleton are as follows: 1) The surface of the F-SiO2 nanoparticles is hydrophobic, but it can be fully infiltrated and stably dispersed in the solvent as described in claim 1; 2) During the process of the PVDF / F-SiO2 composite dispersion spreading to form a film on the surface of the coagulation bath solution as described in claim 1, the water in the coagulation bath will gradually replace the solvent in the PVDF / F-SiO2 composite dispersion, prompting the precipitation and solidification of PVDF to form a porous network skeleton structure; 3) During the process of the water in the coagulation bath gradually replacing the solvent in the PVDF / F-SiO2 composite dispersion, the hydrophobic F-SiO2 nanoparticles will gradually become unstable and precipitate; 4) The fluorinated surface of the F-SiO2 nanoparticles is similar to the fluorinated molecular chain properties of PVDF, and has high interface compatibility, so it can be firmly attached to the surface of the PVDF skeleton.

[0037] Membrane technology plays a vital role in the desalination process, but the membrane materials currently used face two major challenges. On the one hand, due to the insufficient hydrophobicity of the membrane and the weak resistance of the internal structure to wettability, this directly leads to the low efficiency of the membrane in intercepting salt, that is, the salt interception rate is not high. In addition, such membranes are easily contaminated by salt scale, and the pollutants will gradually fill the pores in the membrane, which not only further reduces the effect of salt interception, but also seriously affects the stability of the membrane distillation process, making it difficult to maintain consistent performance in long-term operation. On the other hand, in order to enhance the mechanical strength of the membrane or try to improve its anti-pollution ability, thicker membrane materials are sometimes selected, but this brings another problem: low water flux. The increase in membrane thickness hinders the speed at which water molecules pass through, thereby reducing the fresh water output efficiency of the entire system. These two factors work together to limit the widespread application and effectiveness of membrane distillation technology in the field of seawater desalination.

[0038] Since the membrane materials provided by the prior art and the membrane distillation technology applied in the field of seawater desalination have effects not as good as the inventors expected, the inventors made the present invention through further research.

[0039] The invention selects appropriate amount of hydrophobic fluorinated nano silicon dioxide (F-SiO2) and polyvinylidene fluoride (PVDF) and adds them to N,N-dimethylformamide (DMF) and stirs at 20-25°C to form a PVDF / F-SiO2 composite solution containing 4-14wt% of F-SiO2, extrude and spread the PVDF / F-SiO2 composite solution on the surface of a coagulation bath solution, solidify and dry to obtain a PVDF / F-SiO2 composite film. The thickness of the PVDF / F-SiO2 composite film prepared by the invention can be controlled between 7.5 and 21.4μm, and the porosity can be controlled between 61.1 and 68.6%.

[0040] The inventors further applied the PVDF / F-SiO2 composite membrane prepared by the present invention to the performance characterization of membrane distillation (MD) seawater desalination. The prepared PVDF / F-SiO2 composite membrane was assembled into a membrane distillation device to study the seawater desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The circulation schematic diagram is shown in FIG. Figure 1 As shown (the figure is cited from Tailored PVDF membrane with coordinated interfacial nano / micro-structure for enhanced membrane distillation. Desalination 2024, 573, 117177, https: / / doi.org / 10.1016 / j.desal.2023.117177). Water vapor is condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the seawater desalination system is evaluated based on the salt rejection rate and water flux of the polyvinylidene fluoride based composite membrane, wherein the salt rejection rate and water flux of the polyvinylidene fluoride based composite membrane are calculated from the mass and salinity of the initial seawater and the salinity and mass of the water collected after condensation.

[0041] The following are specific examples of the present invention. The sources of materials involved in the examples and comparative examples are as follows, and the rest are commercially available conventional products unless otherwise specified.

[0042] Fluorinated nano-silica particle size is 7-40nm, CAS number: 112945-52-5, Shanghai Aladdin Technology Co., Ltd.

[0043] Example 1

[0044] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.39g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 5wt%.

[0045] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 5 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0046] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0047] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 1 showed a thickness of 9.7 μm, a porosity of 68.1%, a pore size of 193 nm, a water liquid osmotic pressure (LEPw) of 1.46 bar, and a water contact angle (WCA) of 119°.

[0048] The PVDF / F-SiO2 composite membrane prepared in Example 1 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 16.43 kg / m 2 ·h, the salt rejection rate is 90.1%.

[0049] Example 2

[0050] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.70g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 9wt%.

[0051] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 9 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0052] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0053] The PVDF / F-SiO2 composite membrane with a F-SiO2 content of 9 wt% prepared in Example 2 was observed by using a field emission scanning electron microscope (FESEM) of Hitachi, Japan, Regulus SU8230. The cross-sectional microscopic pore structure was sponge-like pores, and the F-SiO2 content in the pores was appropriate and evenly distributed in the pores without a large amount of agglomeration, as shown in FIG. Figure 2 As shown, the PVDF / F-SiO2 composite membrane has a thickness of 10.4 μm, a porosity of 65.6%, a pore size of 190 nm, a water liquid osmotic pressure (LEPw) of 1.52 bar, and a water contact angle (WCA) of 125° as measured by scanning.

[0054] The PVDF / F-SiO2 composite membrane prepared in Example 2 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 22kg / m 2 ~h, the salt retention rate is 99.9%.

[0055] The possible reasons are: the PVDF / F-SiO2 composite membrane prepared in Example 2 has sponge-like pores and is composed of Figure 2 It can be seen that the F-SiO2 nanoparticles are densely attached to the surface of the PVDF skeleton and do not block the pores, which can greatly improve the hydrophobicity of the pores inside the membrane, thereby effectively improving the membrane's anti-wetting properties, helping to improve the salt rejection rate and maintain high water flux.

[0056] Example 3

[0057] 1) Weigh 50g of DMF and add it to a beaker, weigh 1.01g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution after uniform dispersion, and obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 13wt%.

[0058] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 13 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0059] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0060] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 3 showed a thickness of 11.3 μm, a porosity of 61.8%, a pore size of 186 nm, a water liquid osmotic pressure (LEPw) of 1.50 bar, and a water contact angle (WCA) of 126°.

[0061] The PVDF / F-SiO2 composite membrane prepared in Example 3 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its flux was 18.84 kg / m 2 ·h, the salt rejection rate is 98.3%.

[0062] Comparative Example 1

[0063] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.31g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, after uniform dispersion, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 4wt%.

[0064] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 4 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0065] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0066] The PVDF / F-SiO2 composite membrane with a F-SiO2 content of 9 wt% prepared in Comparative Example 1 was observed using a field emission scanning electron microscope (FESEM) of Hitachi, Japan, and the cross-sectional microscopic pore structure was sponge-like pores, and the F-SiO2 in the pores was evenly distributed but the content was too small. Figure 3 As shown. Figure 2 It can be seen that the thickness of the PVDF / F-SiO2 composite membrane measured by scanning is 8.8μm, the porosity is 69.7%, the pore size is 194nm, the water liquid osmotic pressure (LEPw) is 1.44bar, and the water contact angle (WCA) is 116°.

[0067] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 1 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 15.92kg / m 2 ·h, the salt rejection rate is 90.4%.

[0068] The possible reason is that although the composite membrane prepared in Comparative Example 1 exhibits sponge-like pores, there are very few F-SiO2 nanoparticles on the PVDF skeleton in this "sponge", which are not enough to form a nanoscale rough morphology on the skeleton surface. The improvement in the hydrophobicity of the internal skeleton of the PVDF / F-SiO2 composite membrane is not obvious, and the anti-infiltration property of the pore channels inside the membrane cannot be significantly improved, resulting in a low salt rejection rate.

[0069] Comparative Example 2

[0070] 1) Weigh 50g of DMF and add it to a beaker, weigh 1.09g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, after uniform dispersion, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 14wt%.

[0071] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 14 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0072] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0073] The PVDF / F-SiO2 composite membrane with a F-SiO2 content of 9 wt% prepared in Comparative Example 2 was observed using a field emission scanning electron microscope (FESEM) of Hitachi, Japan, and the cross-sectional microscopic pore structure was sponge-like pores. The F-SiO2 content in the pores was too much, and a large number of agglomerates were generated in the pores, such as Figure 4 As shown, the PVDF / F-SiO2 composite membrane has a thickness of 11.9 μm, a porosity of 60.6%, a pore size of 184 nm, a water liquid osmotic pressure (LEPw) of 1.49 bar, and a water contact angle (WCA) of 130° as measured by scanning.

[0074] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 2 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 17.64kg / m 2 ·h, the salt rejection rate is 97.9%.

[0075] The possible reason is that the PVDF / F-SiO2 composite membrane prepared in Comparative Example 2 has sponge-like pores, but Figure 4 It can be seen that although too many F-SiO2 nanoparticles are densely distributed on the surface of the PVDF skeleton, they also form large aggregates in the pores, resulting in a significant decrease in the water flux of the membrane.

[0076] Example 4

[0077] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.39g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 7.8g of PVDFF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF content of 13.5wt% and a F-SiO2 content of 5wt% PVDF / F-SiO2 composite solution.

[0078] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 5 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0079] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0080] The PVDF / F-SiO2 composite membrane prepared in Example 4 was measured by scanning and found to have a thickness of 19.2 μm, a porosity of 67.5%, a pore size of 185 nm, a water liquid osmotic pressure (LEPw) of 1.86 bar, and a water contact angle (WCA) of 118°.

[0081] The PVDF / F-SiO2 composite membrane prepared in Example 4 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 11.97 kg / m 2 ·h, the salt rejection rate was 91.2%.

[0082] Example 5

[0083] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.70g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 9wt%.

[0084] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 9 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0085] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0086] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 5 showed a thickness of 20.5 μm, a porosity of 64.9%, a pore size of 181 nm, a water liquid osmotic pressure (LEPw) of 1.94 bar, and a water contact angle (WCA) of 122°.

[0087] The PVDF / F-SiO2 composite membrane prepared in Example 5 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 16.25kg / m 2 ·h, the salt rejection rate is 99.9%.

[0088] Example 6

[0089] 1) Weigh 50g of DMF and add it to a beaker, weigh 1.01g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution after uniform dispersion, and obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 13wt%.

[0090] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 13 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0091] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0092] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 6 showed a thickness of 21.4 μm, a porosity of 61.1%, a pore size of 178 nm, a water liquid osmotic pressure (LEPw) of 1.91 bar, and a water contact angle (WCA) of 124°.

[0093] The PVDF / F-SiO2 composite membrane prepared in Example 6 was assembled into a membrane distillation device for seawater desalination performance research. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its flux was 14.01kg / m 2 ·h, the salt rejection rate is 99.3%.

[0094] Comparative Example 3

[0095] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.31g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, after uniform dispersion, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 4wt%.

[0096] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 4 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0097] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0098] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 3 was measured by scanning and found to have a thickness of 18.7 μm, a porosity of 69.2%, a pore size of 187 nm, a water liquid osmotic pressure (LEPw) of 1.85 bar, and a water contact angle (WCA) of 115°.

[0099] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 3 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 10.06kg / m 2 ·h, the salt rejection rate is 90.8%.

[0100] Comparative Example 4

[0101] 1) Weigh 50g of DMF and add it to a beaker, weigh 1.09g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, after uniform dispersion, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 14wt%.

[0102] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 14 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0103] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0104] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Comparative Example 4 showed a thickness of 22.1 μm, a porosity of 59.8%, a pore size of 175 nm, a water liquid osmotic pressure (LEPw) of 1.89 bar, and a water contact angle (WCA) of 130°.

[0105] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 4 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 13.13kg / m 2 ·h, the salt rejection rate is 98.7%.

[0106] Example 7

[0107] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.39g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 5wt%.

[0108] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 5 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0109] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0110] The PVDF / F-SiO2 composite membrane prepared in Example 7 was measured by scanning and found to have a thickness of 16.9 μm, a porosity of 68.3%, a pore size of 188 nm, a water liquid osmotic pressure (LEPw) of 1.69 bar, and a water contact angle (WCA) of 121°.

[0111] The PVDF / F-SiO2 composite membrane prepared in Example 7 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 13.88 kg / m 2 ·h, the salt rejection rate is 90.8%.

[0112] Example 8

[0113] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.70g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 9wt%.

[0114] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 9 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0115] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0116] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 8 showed a thickness of 17.5 μm, a porosity of 65.7%, a pore size of 186 nm, a water liquid osmotic pressure (LEPw) of 1.76 bar, and a water contact angle (WCA) of 127°.

[0117] The PVDF / F-SiO2 composite membrane prepared in Example 8 was assembled into a membrane distillation device for seawater desalination performance research. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 18.6kg / m2 ·h, the salt rejection rate is 99.9%.

[0118] Example 9

[0119] 1) Weigh 50g of DMF and add it to a beaker, weigh 1.01g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution after uniform dispersion, and obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 13wt%.

[0120] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 13 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0121] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0122] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 9 showed a thickness of 18.0 μm, a porosity of 61.4%, a pore size of 183 nm, a water liquid osmotic pressure (LEPw) of 1.74 bar, and a water contact angle (WCA) of 132°.

[0123] The PVDF / F-SiO2 composite membrane prepared in Example 9 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its flux was 14.01kg / m 2 ·h, the salt rejection rate is 99.3%.

[0124] Comparative Example 5

[0125] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.31g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, after uniform dispersion, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 4wt%.

[0126] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 4 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0127] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0128] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 5 was measured by scanning and found to have a thickness of 16.1 μm, a porosity of 69.4%, a pore size of 192 nm, a water liquid osmotic pressure (LEPw) of 1.66 bar, and a water contact angle (WCA) of 120°.

[0129] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 5 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 13.05kg / m 2 ·h, the salt rejection rate is 90.5%.

[0130] Comparative Example 6

[0131] 1) Weigh 50g of DMF and add it to a beaker, weigh 1.09g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, after uniform dispersion, add 7.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 13.5wt% and a F-SiO2 content of 14wt%.

[0132] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 14 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0133] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0134] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Comparative Example 6 showed a thickness of 18.6 μm, a porosity of 60.3%, a pore size of 180 nm, a water liquid osmotic pressure (LEPw) of 1.72 bar, and a water contact angle (WCA) of 130°.

[0135] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 6 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 15.5kg / m 2 ·h, the salt rejection rate is 98.2%.

[0136] Example 10

[0137] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.28g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse it. After it is evenly dispersed, add 5.6g of PVDF and stir for 24 hours to dissolve it into a homogeneous mixed solution to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 10wt% and a F-SiO2 content of 5wt%.

[0138] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 5 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0139] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0140] The PVDF / F-SiO2 composite membrane prepared in Example 10 was measured by scanning and found to have a thickness of 7.5 μm, a porosity of 68.6%, a pore size of 201 nm, a water liquid osmotic pressure (LEPw) of 1.41 bar, and a water contact angle (WCA) of 121°.

[0141] The PVDF / F-SiO2 composite membrane prepared in Example 10 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 17.41 kg / m2 ·h, the salt rejection rate is 90.2%.

[0142] Embodiment 11

[0143] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.50g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 5.6g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF content of 10wt% and a F-SiO2 content of 9wt% PVDF / F-SiO2 composite solution.

[0144] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 9 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0145] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0146] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 11 showed a thickness of 8.3 μm, a porosity of 65.5%, a pore size of 198 nm, a water liquid osmotic pressure (LEPw) of 1.48 bar, and a water contact angle (WCA) of 129°.

[0147] The PVDF / F-SiO2 composite membrane prepared in Example 11 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 22.58 kg / m 2 ·h, the salt rejection rate is 99.4%.

[0148] Example 12

[0149] 1) Weigh 50 g of DMF and add it to a beaker, weigh 0.73 g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 5.6 g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF content of 10 wt% and a F-SiO2 content of 13 wt% PVDF / F-SiO2 composite solution.

[0150] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 13 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0151] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0152] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 12 showed a thickness of 8.9 μm, a porosity of 62.1%, a pore size of 194 nm, a water liquid osmotic pressure (LEPw) of 1.45 bar, and a water contact angle (WCA) of 128°.

[0153] The PVDF / F-SiO2 composite membrane prepared in Example 12 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its flux was 20.67 kg / m 2 ·h, the salt rejection rate is 98.5%.

[0154] Comparative Example 7

[0155] 1) Weigh 50 g of DMF and add it to a beaker, weigh 0.22 g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse it. After it is evenly dispersed, add 5.6 g of PVDF and stir for 24 hours to dissolve it into a homogeneous mixed solution to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 10 wt% and a F-SiO2 content of 4 wt%.

[0156] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 4 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0157] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0158] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 7 was measured by scanning and found to have a thickness of 6.6 μm, a porosity of 69.8%, a pore size of 204 nm, a water liquid osmotic pressure (LEPw) of 1.39 bar, and a water contact angle (WCA) of 118°.

[0159] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 7 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 16.37kg / m 2 ·h, the salt rejection rate was 89.6%.

[0160] Comparative Example 8

[0161] 1) Weigh 50 g of DMF and add it to a beaker, weigh 0.78 g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, after uniform dispersion, add 5.6 g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 10 wt% and a F-SiO2 content of 14 wt%.

[0162] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 14 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0163] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0164] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Comparative Example 8 showed a thickness of 9.6 μm, a porosity of 60.9%, a pore size of 191 nm, a water liquid osmotic pressure (LEPw) of 1.42 bar, and a water contact angle (WCA) of 132°.

[0165] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 8 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 19.67kg / m2 ·h, the salt rejection rate is 97.6%.

[0166] Embodiment 13

[0167] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.28g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse it. After it is evenly dispersed, add 5.6g of PVDF and stir for 24 hours to dissolve it into a homogeneous mixed solution to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 10wt% and a F-SiO2 content of 5wt%.

[0168] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 5 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0169] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0170] The PVDF / F-SiO2 composite membrane prepared in Example 13 was measured by scanning and found to have a thickness of 14.7 μm, a porosity of 67.9%, a pore size of 196 nm, a water liquid osmotic pressure (LEPw) of 1.56 bar, and a water contact angle (WCA) of 123°.

[0171] The PVDF / F-SiO2 composite membrane prepared in Example 13 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 14.2 kg / m 2 ·h, the salt rejection rate is 90.9%.

[0172] Embodiment 14

[0173] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.50g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 5.6g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF content of 10wt% and a F-SiO2 content of 9wt% PVDF / F-SiO2 composite solution.

[0174] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 9 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0175] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0176] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 14 showed a thickness of 15.4 μm, a porosity of 64.8%, a pore size of 193 nm, a water liquid osmotic pressure (LEPw) of 1.61 bar, and a water contact angle (WCA) of 126°.

[0177] The PVDF / F-SiO2 composite membrane prepared in Example 14 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 19.97 kg / m 2 ·h, the salt rejection rate is 99.9%.

[0178] Embodiment 15

[0179] 1) Weigh 50 g of DMF and add it to a beaker, weigh 0.73 g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 5.6 g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF content of 10 wt% and a F-SiO2 content of 13 wt% PVDF / F-SiO2 composite solution.

[0180] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 13 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0181] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0182] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 6 showed a thickness of 15.9 μm, a porosity of 61.4%, a pore size of 191 nm, a water liquid osmotic pressure (LEPw) of 1.60 bar, and a water contact angle (WCA) of 129°.

[0183] The PVDF / F-SiO2 composite membrane prepared in Example 6 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its flux was 18.31 kg / m 2 ·h, the salt rejection rate is 99.1%.

[0184] Comparative Example 9

[0185] 1) Weigh 50 g of DMF and add it to a beaker, weigh 0.22 g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse it. After it is evenly dispersed, add 5.6 g of PVDF and stir for 24 hours to dissolve it into a homogeneous mixed solution to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 10 wt% and a F-SiO2 content of 4 wt%.

[0186] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 4 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0187] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0188] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 9 was measured by scanning and found to have a thickness of 13.8 μm, a porosity of 69.3%, a pore size of 198 nm, a water liquid osmotic pressure (LEPw) of 1.54 bar, and a water contact angle (WCA) of 117°.

[0189] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 9 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 13.69kg / m2 ·h, the salt rejection rate is 90.4%.

[0190] Comparative Example 10

[0191] 1) Weigh 50 g of DMF and add it to a beaker, weigh 0.78 g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, after uniform dispersion, add 5.6 g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 10 wt% and a F-SiO2 content of 14 wt%.

[0192] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 14 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0193] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0194] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Comparative Example 10 showed a thickness of 16.4 μm, a porosity of 60.1%, a pore size of 188 nm, a water liquid osmotic pressure (LEPw) of 1.58 bar, and a water contact angle (WCA) of 131°.

[0195] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 10 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 16.75 kg / m 2 ·h, the salt rejection rate is 98.7%.

[0196] Example 16

[0197] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.28g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse it. After it is evenly dispersed, add 5.6g of PVDF and stir for 24 hours to dissolve it into a homogeneous mixed solution to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 10wt% and a F-SiO2 content of 5wt%.

[0198] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 5 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0199] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0200] The PVDF / F-SiO2 composite membrane prepared in Example 16 was measured by scanning and found to have a thickness of 12.7 μm, a porosity of 68.1%, a pore size of 198 nm, a water liquid osmotic pressure (LEPw) of 1.48 bar, and a water contact angle (WCA) of 118°.

[0201] The PVDF / F-SiO2 composite membrane prepared in Example 16 was assembled into a membrane distillation device to study its desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 15.36 kg / m 2 ·h, the salt rejection rate was 91.4%.

[0202] Embodiment 17

[0203] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.50g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 5.6g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF content of 10wt% and a F-SiO2 content of 9wt% PVDF / F-SiO2 composite solution.

[0204] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 9 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0205] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0206] The PVDF / F-SiO2 composite membrane prepared in Example 17 was measured by scanning to have a thickness of 13.5 μm, a porosity of 65.7%, a pore size of 195 nm, a water liquid osmotic pressure (LEPw) of 1.55 bar, and a water contact angle (WCA) of 121°.

[0207] The PVDF / F-SiO2 composite membrane prepared in Example 17 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 20.89 kg / m 2 ·h, the salt rejection rate is 99.9%.

[0208] Embodiment 18

[0209] 1) Weigh 50 g of DMF and add it to a beaker, weigh 0.73 g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 5.6 g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF content of 10 wt% and a F-SiO2 content of 13 wt% PVDF / F-SiO2 composite solution.

[0210] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 13 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0211] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0212] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 18 showed a thickness of 14.1 μm, a porosity of 61.7%, a pore size of 193 nm, a water liquid osmotic pressure (LEPw) of 1.52 bar, and a water contact angle (WCA) of 126°.

[0213] The PVDF / F-SiO2 composite membrane prepared in Example 18 was assembled into a membrane distillation device for seawater desalination performance research. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its flux was 18.62kg / m 2 ·h, the salt rejection rate is 99.3%.

[0214] Comparative Example 11

[0215] 1) Weigh 50 g of DMF and add it to a beaker, weigh 0.22 g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse it. After it is evenly dispersed, add 5.6 g of PVDF and stir for 24 hours to dissolve it into a homogeneous mixed solution to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 10 wt% and a F-SiO2 content of 4 wt%.

[0216] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 4 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0217] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0218] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 5 was measured by scanning and found to have a thickness of 11.8 μm, a porosity of 69.5%, a pore size of 201 nm, a water liquid osmotic pressure (LEPw) of 1.46 bar, and a water contact angle (WCA) of 119°.

[0219] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 5 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 14.08kg / m 2 ·h, the salt rejection rate is 90.6%.

[0220] Comparative Example 12

[0221] 1) Weigh 50 g of DMF and add it to a beaker, weigh 0.78 g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, after uniform dispersion, add 5.6 g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 10 wt% and a F-SiO2 content of 14 wt%.

[0222] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 14 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0223] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0224] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Comparative Example 12 showed a thickness of 14.9 μm, a porosity of 60.5%, a pore size of 190 nm, a water liquid osmotic pressure (LEPw) of 1.50 bar, and a water contact angle (WCA) of 127°.

[0225] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 12 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 17.14 kg / m 2 ·h, the salt rejection rate is 99.1%.

[0226] Embodiment 19

[0227] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.34g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 6.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF content of 12wt% and a F-SiO2 content of 5wt% PVDF / F-SiO2 composite solution.

[0228] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 5 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0229] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0230] The PVDF / F-SiO2 composite membrane prepared in Example 19 was measured by scanning and found to have a thickness of 8.7 μm, a porosity of 68.4%, a pore size of 198 nm, a water liquid osmotic pressure (LEPw) of 1.45 bar, and a water contact angle (WCA) of 121°.

[0231] The PVDF / F-SiO2 composite membrane prepared in Example 19 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 17.13 kg / m 2 ·h, the salt rejection rate is 90.7%.

[0232] Embodiment 20

[0233] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.61g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 6.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF content of 12wt% and a F-SiO2 content of 9wt% PVDF / F-SiO2 composite solution.

[0234] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 9 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0235] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0236] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 20 showed a thickness of 9.5 μm, a porosity of 65.6%, a pore size of 194 nm, a water liquid osmotic pressure (LEPw) of 1.51 bar, and a water contact angle (WCA) of 125°.

[0237] The PVDF / F-SiO2 composite membrane prepared in Example 20 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 22.23 kg / m 2 ·h, the salt rejection rate is 99.8%.

[0238] Embodiment 21

[0239] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.88g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 6.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 12wt% and a F-SiO2 content of 13wt%.

[0240] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 13 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0241] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0242] The PVDF / F-SiO2 composite membrane prepared in Example 21 was measured by scanning to have a thickness of 9.9 μm, a porosity of 62.2%, a pore size of 192 nm, a water liquid osmotic pressure (LEPw) of 1.49 bar, and a water contact angle (WCA) of 123°.

[0243] The PVDF / F-SiO2 composite membrane prepared in Example 21 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its flux was 20.13 kg / m 2 ·h, the salt rejection rate is 98.9%.

[0244] Comparative Example 13

[0245] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.27g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse it, after it is evenly dispersed, add 6.8g of PVDF and stir for 24 hours to dissolve it into a homogeneous mixed solution, and obtain a PVDF / F-SiO2 composite solution with a PVDF content of 12wt% and a F-SiO2 content of 4wt%.

[0246] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 4 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0247] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0248] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 13 was measured by scanning to have a thickness of 8.0 μm, a porosity of 69.7%, a pore size of 200 nm, a water liquid osmotic pressure (LEPw) of 1.42 bar, and a water contact angle (WCA) of 116°.

[0249] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 13 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 16.05kg / m 2 ·h, the salt rejection rate is 90.2%.

[0250] Comparative Example 14

[0251] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.95g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, after uniform dispersion, add 6.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 12wt% and a F-SiO2 content of 14wt%.

[0252] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 70:30; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 14 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0253] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0254] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Comparative Example 14 showed a thickness of 10.8 μm, a porosity of 60.8%, a pore size of 188 nm, a water liquid osmotic pressure (LEPw) of 1.46 bar, and a water contact angle (WCA) of 126°.

[0255] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 14 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 18.96kg / m 2 ·h, the salt rejection rate is 98.1%.

[0256] Embodiment 22

[0257] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.34g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 6.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF content of 12wt% and a F-SiO2 content of 5wt% PVDF / F-SiO2 composite solution.

[0258] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 5 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0259] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0260] The PVDF / F-SiO2 composite membrane prepared in Example 22 was measured by scanning and found to have a thickness of 18.3 μm, a porosity of 67.7%, a pore size of 193 nm, a water liquid osmotic pressure (LEPw) of 1.83 bar, and a water contact angle (WCA) of 124°.

[0261] The PVDF / F-SiO2 composite membrane prepared in Example 22 was assembled into a membrane distillation device to study its desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 13.56 kg / m 2 ·h, the salt rejection rate was 91.4%.

[0262] Embodiment 23

[0263] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.61g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 6.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF content of 12wt% and a F-SiO2 content of 9wt% PVDF / F-SiO2 composite solution.

[0264] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 9 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0265] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0266] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 23 showed a thickness of 19.1 μm, a porosity of 65.1%, a pore size of 189 nm, a water liquid osmotic pressure (LEPw) of 1.89 bar, and a water contact angle (WCA) of 127°.

[0267] The PVDF / F-SiO2 composite membrane prepared in Example 23 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 17 kg / m 2 ·h, the salt rejection rate is 99.9%.

[0268] Embodiment 24

[0269] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.88g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 6.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 12wt% and a F-SiO2 content of 13wt%.

[0270] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 13 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0271] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0272] The PVDF / F-SiO2 composite membrane prepared in Example 24 was measured by scanning to have a thickness of 19.9 μm, a porosity of 61.6%, a pore size of 187 nm, a water liquid osmotic pressure (LEPw) of 1.86 bar, and a water contact angle (WCA) of 128°.

[0273] The PVDF / F-SiO2 composite membrane prepared in Example 24 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its flux was 15.8 kg / m2 ·h, the salt rejection rate is 99.5%.

[0274] Comparative Example 15

[0275] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.27g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse it, after it is evenly dispersed, add 6.8g of PVDF and stir for 24 hours to dissolve it into a homogeneous mixed solution, and obtain a PVDF / F-SiO2 composite solution with a PVDF content of 12wt% and a F-SiO2 content of 4wt%.

[0276] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 4 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0277] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0278] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 15 was measured by scanning and found to have a thickness of 17.5 μm, a porosity of 69.3%, a pore size of 195 nm, a water liquid osmotic pressure (LEPw) of 1.80 bar, and a water contact angle (WCA) of 120°.

[0279] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 15 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 11.78kg / m 2 ·h, the salt rejection rate is 90.8%.

[0280] Comparative Example 16

[0281] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.95g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, after uniform dispersion, add 6.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 12wt% and a F-SiO2 content of 14wt%.

[0282] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 50:50; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 14 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0283] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0284] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Comparative Example 16 showed a thickness of 20.6 μm, a porosity of 59.7%, a pore size of 183 nm, a water liquid osmotic pressure (LEPw) of 1.84 bar, and a water contact angle (WCA) of 131°.

[0285] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 16 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 14.26kg / m 2 ·h, the salt rejection rate is 98.8%.

[0286] Embodiment 25

[0287] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.34g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 6.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF content of 12wt% and a F-SiO2 content of 5wt% PVDF / F-SiO2 composite solution.

[0288] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 5 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0289] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0290] The PVDF / F-SiO2 composite membrane prepared in Example 25 was measured by scanning and found to have a thickness of 15.5 μm, a porosity of 68.2%, a pore size of 197 nm, a water liquid osmotic pressure (LEPw) of 1.64 bar, and a water contact angle (WCA) of 123°.

[0291] The PVDF / F-SiO2 composite membrane prepared in Example 25 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 14.73 kg / m 2 ·h, the salt rejection rate was 91.1%.

[0292] Embodiment 26

[0293] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.61g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 6.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF content of 12wt% and a F-SiO2 content of 9wt% PVDF / F-SiO2 composite solution.

[0294] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 9 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0295] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0296] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Example 26 showed a thickness of 16.3 μm, a porosity of 65.2%, a pore size of 192 nm, a water liquid osmotic pressure (LEPw) of 1.72 bar, and a water contact angle (WCA) of 124°.

[0297] The PVDF / F-SiO2 composite membrane prepared in Example 26 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 19.39 kg / m 2 ·h, the salt rejection rate is 99.9%.

[0298] Embodiment 27

[0299] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.88g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse, after uniform dispersion, add 6.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 12wt% and a F-SiO2 content of 13wt%.

[0300] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 13 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0301] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0302] The PVDF / F-SiO2 composite membrane prepared in Example 27 was measured by scanning to have a thickness of 17.1 μm, a porosity of 61.8%, a pore size of 189 nm, a water liquid osmotic pressure (LEPw) of 1.69 bar, and a water contact angle (WCA) of 127°.

[0303] The PVDF / F-SiO2 composite membrane prepared in Example 27 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its flux was 18.04 kg / m 2 ·h, the salt rejection rate is 99.2%.

[0304] Comparative Example 17

[0305] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.27g of F-SiO2 and add it to the beaker and stir for 1 hour to disperse it, after it is evenly dispersed, add 6.8g of PVDF and stir for 24 hours to dissolve it into a homogeneous mixed solution, and obtain a PVDF / F-SiO2 composite solution with a PVDF content of 12wt% and a F-SiO2 content of 4wt%.

[0306] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 4 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0307] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0308] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 17 was measured by scanning and found to have a thickness of 14.6 μm, a porosity of 69.4%, a pore size of 199 nm, a water liquid osmotic pressure (LEPw) of 1.63 bar, and a water contact angle (WCA) of 121°.

[0309] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 17 was assembled into a membrane distillation device for seawater desalination performance study. Bohai seawater was heated to 60°C and circulated in the membrane module at a flow rate of 300mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9bar, and the stability of the membrane distillation seawater desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 13.65kg / m 2 ·h, the salt rejection rate is 90.5%.

[0310] Comparative Example 18

[0311] 1) Weigh 50g of DMF and add it to a beaker, weigh 0.95g of F-SiO2 and add it to the beaker, stir and disperse for 1 hour, after uniform dispersion, add 6.8g of PVDF and stir for 24 hours to dissolve into a homogeneous mixed solution, to obtain a PVDF / F-SiO2 composite solution with a PVDF content of 12wt% and a F-SiO2 content of 14wt%.

[0312] 2) Prepare a coagulation bath by mixing DMF and pure water in a mass ratio of 60:40; use a rubber-tipped dropper to slowly pipette the PVDF / F-SiO2 composite solution prepared in the above preparation with a F-SiO2 content of 14 wt% onto the liquid surface of the coagulation bath at room temperature; the PVDF / F-SiO2 composite solution quickly spreads on the liquid surface of the coagulation bath and solidifies into a film.

[0313] 3) The PVDF / F-SiO2 composite membrane prepared in the above step 2) is dried at room temperature for 24 hours to obtain a PVDF / F-SiO2 composite membrane with controllable thickness and pore size.

[0314] Scanning measurements of the PVDF / F-SiO2 composite membrane prepared in Comparative Example 18 showed a thickness of 17.8 μm, a porosity of 60.4%, a pore size of 186 nm, a water liquid osmotic pressure (LEPw) of 1.68 bar, and a water contact angle (WCA) of 130°.

[0315] The PVDF / F-SiO2 composite membrane prepared in Comparative Example 18 was assembled into a membrane distillation device to study the desalination performance. The Bohai Sea water was heated to 60°C and circulated in the membrane module at a flow rate of 300 mL / min. The water vapor was condensed through a 5°C condenser under a vacuum pressure of 0.9 bar, and the stability of the membrane distillation desalination process was analyzed by analyzing the collected water. The test results showed that its water flux was 16.22 kg / m 2 ·h, the salt rejection rate is 98.3%.

[0316] By analyzing Examples 1 to 27 of the present invention and Comparative Examples 1 to 18, it can be seen that the realization process of membrane distillation seawater desalination and the reasons and mechanisms for improving the anti-wetting performance of the hydrophobic fluorinated nano-silica used in the present invention during the membrane distillation process are shown in Figure 5. Figure 5 It can be seen that the hydrophobic fluorinated nano-silica is densely distributed on the surface of the PVDF skeleton. It enhances the hydrophobicity of the skeleton surface and improves the anti-infiltration property of the pores inside the membrane, thereby hindering the movement of the gas-liquid interface into the membrane and preventing salt scale from contaminating the pore structure inside the membrane, thereby improving the stability of membrane distillation seawater desalination.

[0317] By comparing and analyzing Examples 1 to 27 of the present invention and Comparative Examples 1 to 18, Figure 5 It can be seen that:

[0318] (1) When the F-SiO2 content increases, the water contact angle of the PVDF / F-SiO2 composite membrane does not change much, but the LEPw increases accordingly, which increases the mass transfer resistance of water and reduces the possibility of water entering the membrane, thereby improving the stability performance during the seawater desalination process. This is attributed to the fact that the hydrophobic F-SiO2 particles form a superhydrophobic structure in the pores of the PVDF / F-SiO2 composite membrane, which hinders the movement of the gas-liquid interface while increasing the effective gas-liquid evaporation area and improving the water flux.

[0319] (2) With the increase of F-SiO2 content, the LEPw, water flux and salt retention performance of the PVDF / F-SiO2 composite membrane first increase and then decrease. The thickness of the PVDF / F-SiO2 composite membrane does not increase much. Compared with the membrane with a thickness of at least 200 μm in other technologies, the PVDF / F-SiO2 composite membrane of the present invention is kept at an ultra-thin thickness as a whole. The PVDF / F-SiO2 composite membrane with a F-SiO2 content of 9 wt% prepared in Example 2 of the present invention achieves the highest flux and salt retention rate. Even under other conditions, the composite membrane has the relatively optimal performance when the F-SiO2 content is 9 wt%. This is because when the F-SiO2 content is too little, the hydrophobic structure in the pores of the composite membrane cannot be formed, and the gas-liquid interface can easily pass directly through the ultra-thin film. However, when the F-SiO2 content is too high, large agglomerates will be generated, resulting in a decrease in porosity. Moreover, the agglomerates formed by agglomeration will produce defects due to pressure during the membrane distillation seawater desalination process, thereby reducing the salt retention rate.

[0320] In summary, the appropriate F-SiO2 content can obtain a super-hydrophobic structure in the pores of the PVDF / F-SiO2 composite membrane without changing the surface structure. The PVDF / F-SiO2 composite membrane of the present invention can maintain a high hydrophobicity of 22kg / m while maintaining an ultra-thin thickness of 10μm. 2 The flux of 1.5 h and the salt rejection rate of 99.9% show higher flux and long-term stability compared with the conventional commercial membrane produced by Merck Millipore under the same conditions. Figure 6 As shown. Figure 6 It can be seen that the PVDF / F-SiO2 composite membrane of the present invention solves the problem of poor stability of membrane distillation seawater desalination due to insufficient hydrophobicity of traditional membrane materials, as well as the problem of low water flux due to too thick membranes of other technologies.

[0321] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a polyvinylidene fluoride-based composite film, characterized in that: include: Extruding and spreading the polyvinyl difluoride based composite dispersion on the surface of the coagulation bath solution, solidifying into a film, and drying to obtain a polyvinyl difluoride based composite film; The polyvinylidene fluoride composite dispersion is formed by dissolving and dispersing polyvinylidene fluoride and fluorinated nano-silicon dioxide in a solvent, and the mass percentage concentration of the polyvinylidene fluoride is 10 to 13.5 wt %; The coagulation bath solution is formed by dissolving a solvent in water. In terms of mass percentage, the mass ratio of the solvent to the water is 50-70:50-30.

2. The method for preparing a polyvinylidene fluoride-based composite film according to claim 1, characterized in that: The fluorinated nano-silicon dioxide accounts for 5 to 13 wt% of the mass of the polyvinylidene fluoride; the fluorinated nano-silicon dioxide is selected from hydrophobic fluorinated nano-silicon dioxide with a particle size of 7 to 40 nm.

3. The method for preparing a polyvinylidene fluoride-based composite film according to claim 1, characterized in that: The solvent is selected from at least one of N-methylpyrrolidone, N,N-dimethylformamide, dimethylacetamide, dimethyl sulfoxide, cyclohexanone and tetrahydrofuran.

4. A polyvinylidene fluoride-based composite film, characterized in that: The polyvinylidene fluoride composite film is prepared by the preparation method according to any one of claims 1 to 3; The polyvinylidene fluoride-based composite membrane has a thickness of 6.6 to 22.1 μm, a porosity of 59.7 to 69.8%, and a water contact angle of 116 to 132°.

5. Use of the polyvinylidene fluoride based composite membrane as claimed in claim 4 in seawater desalination.

6. A seawater desalination system, comprising a membrane distillation seawater desalination device, characterized in that: It also includes the polyvinylidene fluoride-based composite film as claimed in claim 4.

7. The seawater desalination system according to claim 6, characterized in that: The membrane distillation seawater desalination device comprises a membrane module, and the membrane module is used to be equipped with a polyvinylidene fluoride-based composite membrane.

8. A method for desalination of seawater, characterized in that: The method comprises: placing the heated seawater in the system as claimed in claim 6 or 7 for circulation, condensing, and obtaining desalinated seawater.

9. A stability evaluation method, characterized in that: The stability evaluation method is used to evaluate the seawater desalination system according to claim 6 or 7, and the method comprises: Evaluating the stability of the seawater desalination system according to the salt rejection rate and water flux of the polyvinylidene fluoride based composite membrane; The salt rejection rate of the polyvinylidene fluoride-based composite membrane is calculated by the salt content of the initial seawater and the salt content of the water collected after condensation, and the calculation formula is shown in formula (I): R=(1-C P / C F )×100% (I), In formula (I), R is the salt rejection rate, C F is the initial seawater salinity, C P is the salt content of the water collected after condensation; The water flux of the polyvinylidene fluoride-based composite membrane is the mass of water collected after condensation.

10. The stability evaluation method according to claim 9, characterized in that: The polyvinylidene fluoride composite membrane has a salt rejection rate of 89.6-99.9% and a water flux of 10.06-22.58 kg / m 2 ·h.

Citation Information

Patent Citations

  • Method for preparing polymer film

    CN116751382B

  • Method for preparing superhydrophobic film through spray deposition

    CN110170252A

  • Super-hydrophobic silica aerogel and preparation method thereof, super-hydrophobic porous membrane and preparation method and application thereof

    CN113213492A

  • Preparation method of polymer film

    CN116751382A

  • Method for preparing hydrophobic fluorinated mixed matrix membranes, said membranes, and separation methods using said membranes

    EP2668995A1